HUBUNGAN KARAKTERISTIK PASIEN HUMAN IMMUNODEFICIANCY VIRUS (HIV) DENGAN PENGAMBILAN KEPUTUSAN PENGOBATAN DI PUSKESMAS DUPAK - Sindi Paratika (Universitas Airlangga, 2018)
Dupak primary health care is one of health care which have complete HIV and Acquired Immuno Deficiency Syndrom (AIDS) prevention program. The number of HIV-AIDS sufferers increasing every year, but the number of new HIV positive cases taking Anti Retroviral Virus(ARV) treatment at Dupak primary health care are low. The purpose of this research was analyzed the HIV treatment decision making process of patients at Dupak primary health care. The method in this research was descriptive quantitive research through questionnaires. Variables of this study are individual characteristics include age, level of education, knowledges, status of severity with decision making process of treatment. The results of this study indicate that most respondents (50%) have a high knowledge of HIV treatment. Decision-making process of HIV positive patient treatment have 2 stages that most respondents didn’t do. There are stage of the information search (75%) and stage of alternative evaluation (56.25%). The conclusion of this research are most respondents didn’t do information searching and alternative evaluation in decision making process at Dupak primary health care. According suggested from this study are to improve HIV related socialization programs through promotional activities and discussions related to HIV treatment services to improve knowledge and activeness of seeking information through print and electronic media.